The development, validation and standardisation of a questionnaire measuring an Auditing teaching-learning intervention at a SAICA-accredited university - Stumke, O.; Moolman, A. M.; Leendertz, V. (South African Journal of Higher Education, 2023)
Questionnaires are widely used in the Accountancy field as a data collection instrument. However, previous studies have contentious views on the reliability of questionnaires in academic studies. This study describes the development of a custom-made questionnaire to evaluate the effectiveness of a teaching-learning intervention, the Audit Cube, designed to affect the knowledge, skills, attitudes and values of Auditing of B.Com. honours students in the Accountancy field at a SAICA-accredited university. The questionnaire was distributed to 156 university honours students, whereafter it was validated and standardised. Most of the extracted factors indicated a reliability level higher than 0.9, signifying that the constructs were suitable to address the project’s research question and that the questionnaire is valid. In conclusion, this study found that the use of questionnaires in academic studies is deemed reliable if a standardised process is followed in its development. Consequently, the study suggests that custom-made questionnaires should undergo factor analysis to prove the instrument’s validity prior to reporting on the findings. The findings of this study may be useful to academics in providing guidelines in developing their own data collection instrument to measure the effectiveness of a teaching-learning intervention and may also support the use of questionnaires by researchers in the teaching-learning environment.